nếu 7-3x/5=y+4/3=6x-y/5.tìm x/y
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\Leftrightarrow-\frac{3x-7}{5}=\frac{y+4}{3}\)
\(\Rightarrow-\frac{y+4}{3}-\frac{3x-7}{5}=0\)
\(\Rightarrow-\frac{5y+9x-1}{15}=0\)
\(\Rightarrow5y+9x-1=0\)
\(\Rightarrow\frac{y+4}{3}=-\frac{y-6x}{5}\)
\(\Rightarrow\frac{y+4}{3}-\left(-\frac{y-6x}{5}\right)=0\)
\(\Rightarrow\frac{2\left(4y-9x+10\right)}{15}=0\)
\(\Rightarrow2\left(4y-9x+10\right)=10\)
\(\Rightarrow4y-9x+10=0\)
=>\(y=-1\); \(x=\frac{2}{3}\)
\(\Leftrightarrow\frac{7-3x}{5}=\frac{y+4}{3}=\frac{6x-y}{5}\)
\(\Rightarrow\frac{-3x-7}{5}=\frac{y+4}{3}\)
\(\Rightarrow\frac{-y+4}{3}-\frac{3x-7}{5}=0\)
\(\Leftrightarrow\frac{-5y+9x-1}{15}=0\)<=>5y+9x-1=0
\(\Rightarrow\frac{y+4}{3}=\frac{-y-6x}{5}\)
\(\Rightarrow\frac{y+4}{3}-\left(\frac{-y-6x}{5}\right)=0\)
\(\Leftrightarrow\frac{2\left(4y-9x+10\right)}{15}=0\)
=>2(4y-9x+10)=0
=>4y-9x+10=0
=>x=\(\frac{2}{3}\);y=-1
a) Để y nguyên thì \(6x-4⋮2x+3\)
\(\Leftrightarrow-13⋮2x+3\)
\(\Leftrightarrow2x+3\in\left\{1;-1;13;-13\right\}\)
\(\Leftrightarrow2x\in\left\{-2;-4;10;-16\right\}\)
hay \(x\in\left\{-1;-2;5;-8\right\}\)
1,x/7=y/3 va x-24=y
=>x/7=y/3 va x-y=24
adtcdts=n:
x/7=y/3=x-y/7-3=24/4=6
Suy ra :x/7=6=>x=6.742
y/3=6=>y=3.6=18
2,Adtcdts=n:
x/5=y/7=z/2=y-x/7-5=48/2=24
suy ra : x/5=24=>x=120
y/7=24=>y=168
z/2=24=>z=48
Tìm x:
1. 3x (2x + 3) - (2x + 5).(3x - 2) = 8
\(\Leftrightarrow6x^2+9x-6x^2+4x-15x+10=0 \)
\(\Leftrightarrow-2x+10=0\Leftrightarrow x=5\)
Vậy x = 5
2. 4x (x -1) - 3(x2 - 5) -x2 = (x - 3) - (x + 4)
\(\Leftrightarrow4x^2-4x-3x^2+15-x^2=x-3-x-4\)
\(\Leftrightarrow-4x+15=-7\)
\(\Leftrightarrow-4x=-22\Leftrightarrow x=\frac{11}{2}\)
Vậy x = \(\frac{11}{2}\)
3. 2 (3x -1) (2x +5) - 6 (2x - 1) (x + 2) = -6
\(\Leftrightarrow2\left(6x^2+15x-2x-5\right)-6\left(2x^2+4x-x-2\right)=-6\)
\(\Leftrightarrow12x^2+30x-4x-10-12x^2-24x+6x+12=-6\)
\(\Leftrightarrow8x=-8\Leftrightarrow x=-1\)
Vậy x = -1
4. 3 ( 2x - 1) (3x - 1) - (2x - 3) (9x - 1) - 3 = -3
\(\Leftrightarrow3\left(6x^2-2x-3x+1\right)-18x^2+2x+27x-3-3=-3\)
\(\Leftrightarrow18x^2-6x-9x+3-18x^2+2x+27x-6=-3\)
\(\Leftrightarrow14x=0\Leftrightarrow x=0\)
Vậy x = 0
5. (3x - 1) (2x + 7) - ( x + 1) (6x - 5) = (x + 2) - (x - 5)
\(\Leftrightarrow6x^2+21x-2x-7-6x^2+5x-6x+5=7\)
\(\Leftrightarrow18x=9\Leftrightarrow x=\frac{1}{2}\)
Vậy x = \(\frac{1}{2}\)
6. 3xy (x + y) - (x + y) (x2 + y2 + 2xy) + y3 = 27
\(\Leftrightarrow3x^2y+3xy^2-\left(x+y\right)^3+y^3=27\)
\(\Leftrightarrow3x^2y+3xy^2-x^3-y^3-3x^2y-3xy^2+y^3=27\)
\(\Leftrightarrow-x^3=27\)
\(\Leftrightarrow x=-3\)
Vậy x = -3
7. 3x (8x - 4) - 6x (4x - 3) = 30
\(\Leftrightarrow24x^2-12x-24x^2+12x=30\)
\(\Leftrightarrow0=30\) ( vô lý)
Vậy pt vô nghiệm
8. 3x (5 - 2x) + 2x (3x - 5) = 20
\(\Leftrightarrow15x-6x^2+6x^2-10x=20\)
\(\Leftrightarrow5x=20\Leftrightarrow x=4\)
Vậy x = 4